2009
DOI: 10.1103/physrevlett.103.217002
|View full text |Cite
|
Sign up to set email alerts
|

Dissipative Enhancement of the Supercurrent inTl2Ba2CaCu2O8Intrinsic Josephson Junctions

Abstract: We have measured dissipation-induced localization of the reaction coordinate for a metastable-state decay process in a model system with moderate damping. Specifically, the supercurrent in an array of Tl2Ba2CaCu2O8 intrinsic Josephson junctions is larger when all the junctions are in the zero-voltage state than when one or more junctions are in the voltage state since the dissipation is larger in the former case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…The slight suppression of the switching current as the branch number n increases is probably due to Ohmic heating. The switching current on the supercurrent branch (n = 0) is larger (66 µA) as is commonly observed in measurements of IJJ stacks [11,13]. From fits to switching current distributions (not shown) we find the unfluctuated critical current to be I C = 80 µA, and hence the plasma frequency,…”
Section: Figsupporting
confidence: 59%
“…The slight suppression of the switching current as the branch number n increases is probably due to Ohmic heating. The switching current on the supercurrent branch (n = 0) is larger (66 µA) as is commonly observed in measurements of IJJ stacks [11,13]. From fits to switching current distributions (not shown) we find the unfluctuated critical current to be I C = 80 µA, and hence the plasma frequency,…”
Section: Figsupporting
confidence: 59%
“…A rare exception is the c-axis transport in extremely anisotropic layered cuprates. Single crystals of Bi-, Tl-, 31,32 and Hg-based 33 cuprates represent natural stacks of atomic scale intrinsic tunnel junctions. The intrinsic tunneling spectroscopy (ITS) provides a unique opportunity to probe directly bulk electronic spectra of cuprates.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] The most striking feature is that a crossover temperature, T cr , to the MQT state in the phase switch from the first to the second resistive branch (2nd SW) is largely enhanced compared to that from the zero voltage to the first resistive branch (1st SW) in the multi-branched current-voltage (I-V) characteristics of IJJs. [6][7][8][9][10][11][12][13][14][15] An early study 6) suggested that such an enhancement was due to the self-heating effects in the first resistive state, based on the consideration that a series array of uniform Josephson junctions should show the same value of T cr as long as the current flowing in each junction agrees with the externally-applied bias current.However, the anomalous increase of T 2nd cr was found to be independent of the device structure of IJJs with different heat-transfer environment 7) and the order of phase switches, 10) throwing doubt on the self-heating effects after the 1st SW.…”
mentioning
confidence: 99%